Pengujian 15 Genotipe Kedelai pada Kondisi Intensitas Cahaya 50% dan Penilaian Karakter Tanaman Berdasarkan Fenotipnya - Susanto, Gatut Wahyu Anggoro; Sundari, Titik (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTThe Examination of 15 Soybean Genotypes at 50% Light Intensity and Evaluation of CropâsPhenotypic Characters. Sunlight is one of the important plant growth requirements. In orderto understand morphological character changes in the crops due to different light intensity, 15genotypes of soybean consisted of Willis, D3578-3/3072-11, Seulawah, Aochi/W-62, Kaba,IAC 100/Brr-1, MLGG 0081, MLGG 0059, MLGG 0120, 9837/Kawi, D-6-185, IAC 100, MLGG0383-1, Pangrango, MLGG 0069 and MLGG 0122 were tested. The research was conducted inKendalpayak (grey Alluvial soil type, 450 above sea level, C3 climate type), Malang at dryseason in 2006. The research design was Randomize Complete Block under two differentenvironmental conditions, with three replications. The experiment was conducted under fulland 50 %light intensity. The results indicated that the reduction of light intensity as much as50 % resulted in some changes in phenotypic characters such as size and lifespan of the 15genotype being tested, included the increase of plant height, the longer distance betweennodes, the decrease in node number, the smaller size of stem diameter, the decrease on thenumber of leaves, the narrower of the leaf âs width and the decrease in pod number. Lessenedseed weight, the low weight of 100 seeds, the lowering level of the leafâs greenness, and theaccelerate age of flowering and harvesting. IAC 100, MLGG 0383-1 and IAC 100/BBR-1 producedhigh under 50% of light intensity.Keywords : Soybean (Glycine max (L) Merrill), light intensity, phenotypic